Toxic tau: structural origins of tau aggregation in Alzheimer's disease - Mamun, Abdullah; Uddin, Md; Mathew, Bijo; Ashraf, Ghulam (Neural regeneration research, 2020)
Alzheimer's disease is characterized by the extracellular accumulation of the amyloid β in the form of amyloid plaques and the intracellular deposition of the microtubule-associated protein tau in the form of neurofibrillary tangles. Most of the Alzheimer's drugs targeting amyloid β have been failed in clinical trials. Particularly, tau pathology connects greatly in the pathogenesis of Alzheimer's disease. Tau protein enhances the stabilization of microtubules that leads to the appropriate function of the neuron. Changes in the quantity or the conformation of tau protein could affect its function as a microtubules stabilizer and some of the processes wherein it is involved. The molecular mechanisms leading to the accumulation of tau are principally signified by numerous posttranslational modifications that change its conformation and structural state. Therefore, aberrant phosphorylation, as well as truncation of tau protein, has come into focus as significant mechanisms that make tau protein in a pathological entity. Furthermore, the shape-shifting nature of tau advocates to comprehend the progression of Alzheimer's disease precisely. In this review, we emphasize the recent studies about the toxic and shape-shifting nature of tau in the pathogenesis of Alzheimer's disease.